SISTEM INFORMASI KELOMPOK USAHA BERSAMA NELAYAN PADA DINAS KELAUTAN PERIKANAN KABUPATEN BANGKA BERBASIS DEKSTOP: INFORMATION SYSTEM, JOINT BUSINESS GROUP, MARINE FISHERIES SERVICE, FISHERMEN - Dendi Rachmatsyah, Agus (FORTECH (Journal of Information Technology), 2018)
The design of information systems of business groups together with fishermen based on DEKSTOP on the Department of Marine and Fisheries in Bangka Regency seeks to improve information services to fishermen in the Bangka Marine and Fisheries Service, so that the fishermen's data is easier to access fishermen's information. The purpose of this study is to develop services to the community, especially fishermen in the field of marine and fisheries, to facilitate services and provide encouragement in the development, development, coaching of joint fisheries business groups, especially in Bangka district. In responding to the problems that occur in the fishermen, he uses several research methods that can help solve this problem, namely by using survey research so that the data of the fishermen will be collected later in the process, then will produce an object oriented system that can be clearly defined so that fishermen can be more efficient in time utilization